Retrospective Comparison between the Effects of Propofol and Inhalation Anesthetics on Postoperative Recurrence of Early- and Intermediate-Stage Hepatocellular Carcinoma - Koo, Bon-Wook; Lim, Dae-Jin; Oh, Ah-Young; Na, Hyo-Seok (Medical principles and practice, 2020)
Objective: Previous studies have reported that propofol has antitumor, anti-inflammatory, and antioxidant effects in addition to its anesthetic properties. To confirm this, a retrospective investigation was conducted to determine whether different anesthetic agents, particularly propofol and inhalation anesthetics, have an effect on the recurrence of hepatocellular carcinoma (HCC) in patients who were diagnosed with primary HCC and underwent laparoscopic hepatectomy. Subjects and Methods: Patients with Barcelona Clinic Liver Cancer stages 0, A, and B HCC, who underwent laparoscopic hepatic resection, were enrolled in this study. Postoperative HCC recurrence, which was determined from postoperative liver CT, was evaluated 24 months postoperatively with respect to the main anesthetic agents. The characteristics of HCC and other patient-related or surgery-related variables were evaluated together. Results and Conclusion: During the 24-month period after hepatic resection, less HCC patients in the propofol group than in the inhalation group recurred (p = 0.046). The mean time to recurrence was 20.8 months (95% CI, 19.7–22.0) and 19.1 months (95% CI, 17.8–20.4) in the propofol group and the inhalation group, respectively. In addition, multivariable Cox proportional regression analysis revealed that the propofol group showed significantly decreased recurrence versus the inhalation group (hazard ratio, 0.57; 95% CI, 0.47–0.69; p = 0.029). When propofol was used as the main general anesthetic agent for laparoscopic hepatic resection, the postoperative 2-year recurrence rate decreased in early- and intermediate-stage HCC.